2001
DOI: 10.1063/1.1337092
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the exponential distribution of traps in glass

Abstract: A recent rigorous analysis of the broad thermoluminescence (TL) peak of a Brown microcline has shown it to be due to an exponential distribution of traps. Incidentally, from the statistical point of view one expects the traps to follow a Gaussian distribution. In order to elucidate the origin of the exponential trap distribution we have analyzed a set of glow peaks of a light green glass recorded under varying conditions of trap filling. The sample upon γ-rays irradiation (dose=7×103 Gy) exhibits a broad TL pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…The continuous and/or closely spaced trap distribution determined from IRM is characteristic of the amorphous or polycrystalline material. The main effect of the continuous distributions of traps is a broadening of the glow peak .A recent rigorous analysis of the broad TL peak invoked on the other hand that it is apparently due to an exponential distribution of traps [18][19][20]. The origin of trap distribution is not profoundly, but it can be considered a Gaussian distribution from a statistical standpoint in polycrystalline materials.…”
Section: Trap Distributionmentioning
confidence: 98%
“…The continuous and/or closely spaced trap distribution determined from IRM is characteristic of the amorphous or polycrystalline material. The main effect of the continuous distributions of traps is a broadening of the glow peak .A recent rigorous analysis of the broad TL peak invoked on the other hand that it is apparently due to an exponential distribution of traps [18][19][20]. The origin of trap distribution is not profoundly, but it can be considered a Gaussian distribution from a statistical standpoint in polycrystalline materials.…”
Section: Trap Distributionmentioning
confidence: 98%
“…In this case, the trap level is not regarded as a discrete energy level located in the band gap of the host material, but rather a continuum of energy levels around a certain mean value. This possibility has been explored by various authors, 21,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and three main types of trap distributions have been considered: uniform, exponential, and Gaussian profiles.…”
Section: Continuous Trap Depth Distributionsmentioning
confidence: 99%
“…Sakurai et al 34 found proof for an exponential trap profile in brown microcline, but later showed that this exponential profile was in fact only the deeper side of a Gaussian distribution. 35 This information on the shape of the distribution can be obtained by integrating the glow curves for various excitation temperatures. The surface under the glow curve is a measure for the total number of luminescent ions returning to the ground state during the TL experiment, and hence for the total number of trapped charge carriers.…”
Section: Combining Tl and Initial Rise Analysis For Trap Depth Spementioning
confidence: 99%
“…The main effect of the continuous distributions of traps is a broadening of the glow peak. A recent rigorous analysis of the broad TL peak of a Brown microcline has shown that it to be due to an exponential distribution of traps [17,18]. Nevertheless, a Gaussian distribution is likely to exist in polycrystalline or amorphous materials from a statistical standpoint.…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, a Gaussian distribution is likely to exist in polycrystalline or amorphous materials from a statistical standpoint. In order to elucidate the origin of the trap distribution of Brown microcline, Sakurai and Gartia [17,18] obtained that the broad peak becomes narrower once a thermal cleaning technique is applied to the irradiated specimen, and the application of CGCD reveals the Gaussian distribution of traps definitely gives better results for glow curves at the beginning of the stopping temperature, than the exponential distribution However, the exponential distribution of traps provides better fit with the TL glow curves that were obtained after application of high stopping temperature than the Gaussian distribution does. This means that the thermal cleaning depletes the shallower traps without affecting the deeper ones and, therefore, the trap distribution is initially Gaussian, but in thermally cleaned glow curves the distribution of the traps is found to be exponential.…”
Section: Resultsmentioning
confidence: 99%